Peran Mata Pelajaran Seni Budaya (Seni Teater) Sebagai Pembentuk Karakter Siswa pada Siswa Kelas X SAMN 11 Palembang - Pratiwi, Lilis; Hasan, Hasan; Ilhaq, Muhsin (Institut Teknologi Pendidikan Indonesia, 2022)
This research was carried out to know the learning process in the art and culture subject (theater arts) for class X SMAN 11 Palembang as forming student character. This study used a qualitative descriptive research method and used one teacher as a resource, namely Mrs. Yulia Sari S. Pd as one of the class X arts and culture teachers. Based on the results of the research conducted, students responded well to theater learning, therefore the character contributed by the art and culture subject (theater arts) of class X students in the even semester of the 2022/2023 academic year SMA Negeri 11 Palembang through traditional theater learning activities, spiritual values, collaboration, responsibility, discipline, and creative.